Effect of uniaxial compressive strength of rock on penetration rate and bit wear rate of drill - Sahoo S.K.; Choudhary B.S. (My University, 2025)
Drillability plays a crucial role in increasing the capability of blasthole drills in drilling and thereby contributing valuable input for the mining industry. The productivity of the mines and the life of the machines are directly dependent on the wear rate of the drill bit. In this light, an investigation was conducted to illustrate the relationship between the uniaxial compressive strength (UCS) of the rock, the penetration rate of the drilling machine and the bit wear-out rate at overburden benches of a surface coal mine. The wear-out rate of drilling bit estimated from digital imaging of the diametrical distribution of button bits obtained from imaging software, that was taken 'Before' and 'After' drilling. The UCS of rock mass was measured using Schmidt Hammer while wear-out rate of the drill bit was measured through computer software. The results obtained from the experimental observations and graphical plot shows that as the UCS (in N/mm2) increasing from 27.5 to 42.46 the penetration rate (in mm/s) decreases from the 30 to 14 and wear-out rate (in mm2/meter of the hole drilled) are increasing from 0.339 to 1.05.